Prospects of wheat flour in improving the economy of the Labuandiri village Siontapina district, Buton regency, Indonesia - Purnamasari, Wa Ode Dian; Al Zarliani, Wa Ode; Wardana, Wardana; Anggraini, Anggraini (Institute for Research and Community Service (LPPM), Universitas Islam Madura, Indonesia, 2024)
The production of raw crackers made from wheat flour has developed as a potential small business in Labuandiri Village, Buton Regency. In the context of business development, it is important to know to what extent the production process is able to create added value for craftsmen. The problem formulation in this research is how much added value results from converting wheat flour into raw crackers. This research aims to analyze the added value of converting wheat flour into raw crackers in Labuandiri Village, Siotapina District, Buton Regency, using the Hayami method. The sample consisted of 10 participants selected purposively. Data collection techniques include observation, interviews and documentation. The results show that the average production of raw crackers is 56 kg per month with 48 kg of raw materials and involving 1.8–2 workers. The resulting added value is 1.11/kg of raw materials, with a profit of 0.84/kg and labor compensation of 0.27/kg. This research is expected to provide insight for craftsmen and stakeholders about the potential for added value and encourage the development of small businesses to increase the income of local craftsmen.